Ἕως οὗ como introductor de oración en Herodoto II,143, 4 y Corpus Hippocraticum Morb. IV, 51 (Minerva, 2019)
In this article the author defends the reading έως ού, which appears in one group of manuscripts of Herodotus. Though this construction is commonly thought to be used only from the hellenistic period, two other examples are found in the classical age. The occurrence of this construction also in the hippocratic treatise Morb. IV should make us establish new conclusions about the ionic dialect and the development of the κοινή.